Infeksi Ektoparasit dan Korelasinya dengan Panjang, Berat, dan Faktor Kondisi Benih Ikan Mas Merah Najawa (Cyprinus carpio Linneaus) - Vaediyasari, Dahniar; Setyawan, Agung Cahyo; Astuti, Astuti; Syakuri, Hamdan (MAIYAH, 2024)
One of the problems in commona carp farming activities is ectoparasite infection which is thought to correlate with length, weight and condition of the fish. The aims of the research were to determine the species, prevalence, intensity and dominance of ectoparasites and to determine the correlation between the number of ectoparasites and the length, weight and condition factors of Najawa red carp (Cyprinus carpio Linneaus) fingerling at BPTPB Cangkringan. The research used laboratory observation method on randomly selected fish samples. Sampling was carried out for 3 weeks and a total of 27 individuals were examined. Ectoparasite observations were carried out on mucus samples from the body surface and gill sheets microscopically. The length and weight of each fish sample were measured and the results were used to calculate the condition factor. The correlation relationship was calculated between the number of ectoparasites and the length, weight and condition factors of the fish. The research results showed that five ectoparasites were found to infect fish samples with varying prevalence and intensity values, namely Trichodina sp., Dactylogyrus sp., Gyrodactylus sp., Glochidium sp. and Vorticella sp. Trichodina sp. has the highest prevalence, intensity and dominance compared to other parasites. The number of ectoparasites has a positive correlation with the length and weight of fish in the low category. In addition, a low negative correlation was found between the number of ectoparasites and fish condition factor. The results of this study indicate that ectoparasites are a factor that can influence the productivity of Najawa red carp cultivation.